‘We are the forgotten ones’: Occupational stress among university secretaries in Botswana - Ilse E. Plattner (SA Journal of Human Resource Management, 2010)
Orientation: Secretaries play an essential role in any work organisation, but their contributions and support in the daily management activities are not always recognised. Research purpose: There is little research on occupational stress among secretaries. Therefore, this study aimed to investigate work-related stressors in the secretarial profession and their association with psychosomatic complaints.